Neonatal Bacille Calmette-Guérin Vaccination and Infections in the First Year of Life: The MIS BAIR Randomized Controlled Trial. (19th June 2021) - Messina, Nicole L; Pittet, Laure F; Gardiner, Kaya; Freyne, Bridget; Francis, Kate L; Zufferey, Christel; Abruzzo, Veronica; Morrison, Clare; Allen, Katrina J; Flanagan, Katie L; Ponsonby, Anne-Louise; Robins-Browne, Roy; et al.
Abstract: Background: Bacille Calmette-Guérin (BCG) vaccination has beneficial off-target effects that may include protecting against non-mycobacterial infectious diseases. We aimed to determine whether neonatal BCG vaccination reduces lower respiratory tract infections (LRTI) in infants in the Melbourne Infant Study: BCG for Allergy and Infection Reduction (MIS BAIR) trial. Methods: In this investigator-blinded trial, neonates in Australia were randomized to receive BCG-Denmark vaccination or no BCG at birth. Episodes of LRTI were determined by symptoms reported in parent-completed, 3-month questionnaires over the first year of life. Data were analyzed by intention-to-treat using binary regression. Results: A total of 1272 neonates were randomized to the BCG vaccination (n = 637) or control (n = 635) group. The proportion of participants with an episode of LRTI in the first year of life among BCG-vaccinated infants was 54.8% compared to 58.0% in the control group, resulting in a risk difference of −3.2 (95% confidence interval, −9.0 to 2.6) after multiple imputation. There was no interaction observed between the primary outcome and sex, maternal BCG, or the other prespecified effect modifiers. Conclusions: Based on the findings of this trial, there is insufficient evidence to support the use of neonatal BCG vaccination to prevent LRTI in the first year of life in high-income settings. Abstract : In an RCT in a high-income setting (with neonatal HepB vaccination), infants randomized to neonatal BCG vaccination had a small, −3.2 (95% CI, −9.0 to 2.6), reduction in the risk of respiratory tract infection in the first year of life.